Dependencies among environmental performance indicators for buildings and their implications. (October 2017) - Dias, W.P.S.; Chandratilake, S.R.; Ofori, George
Abstract: Environmental performance rating schemes such as LEED allocate separate indicator scores for various criteria (or aspects). The overall environmental performance score is obtained by summing these separate scores. However, no mention is made regarding any dependencies among aspect indicators. In this study, possible influences, including their degree ('strong', 'moderate', and 'none') and direction (positive, negative) were identified among the seven aspects covering the sustainability of the building site (i.e. Site domain) in an environmental performance assessment scheme for buildings. These judgements were corroborated by the correlation coefficients corresponding to scores for those aspects achieved by 10 buildings. First and higher order influences were accounted for through a matrix-based scheme, which revealed aspects that were influencing others or being influenced by them. The degree of influencing other aspects was found to be inversely proportional to that of being influenced by them. The aspect weights, obtained by querying experts, appeared to be independent of their degree of influence. The negative dependencies in this Site domain gave rise to constraints on combinations of aspect scores and the maximum environmental performance score achievable. The score levels that would maximize this overall score were obtained through an optimization exercise; this generated some possible planning strategies. Highlights: High correlation between indicator scores may reflect indicator dependency. Correlation coefficients are used to confirm the identified degrees of influence. Direct and higher order influences are computed using matrix manipulations. Negative dependencies constrain the achievable environmental performance score. Results of constrained optimizations can be used to arrive at planning strategies.